Women and Wage Labour in a Period of Transition: Montreal, 1861-1881 - Bradbury, Bettina (Canadian Labour History: Selected Readings, 1994)
NOTICE DG
Keywords: Famille; Femmes; Travail

Working Families: Age, Gender and Daily Survival in Industrializing Montreal - Bradbury, Bettina (Labour / Le travail, 1994)
Keywords: Famille; Femmes

SHEARER, JAMES - McNally, Larry S. (Dictionnaire biographique du Canada, 1994)

RODIER, JOSEPH-ALPHONSE - Rouillard, Jacques (Dictionnaire biographique du Canada, 1994)

ARCHAMBAULT, LOUIS - Comeau, Robert (Dictionnaire biographique du Canada, 1994)

JULIEN, HENRI - Guilbault, Nicole (Dictionnaire biographique du Canada, 1994)